An Automatic Detection and Notification of Potholes on Roads to Avoid Disasters - Ms. Nandini S., Mr. Yathish D. P., Mr. Manikanta K. B., Mrs. Mala B. M. (International Journal of Advanced Science and Technology, 2020)
The development of the country  depends on its economical  growth. The major means of transportation  plays a vital role for the economical development of a country.  The roads play a predominant means of transportation for many developing countries.  The well maintained roads reflect the economy as well as status of those countries. As roads are to be maintained properly, the potholes in the roads should be identified and repaired quickly.  In this paper, we are proposing a system  which offers a cost effective solution to identify the potholes present in the roads . The proposed system consists of Arduino Uno[8] with ATmega16U2[9]  as microcontroller which has ultra sonic sensor to detect the potholes on the roads. The GSM SIM800A[10] module is used to send the message with the exact location of the pothole identified by GPS SIM28ML[11] module which is attached to the bottom of the vehicle. The threshold value is set to the sensor present at the bottom of the vehicle. If pothole identified, there will be variation in the threshold value  which in turn trigger the arduino to send the message with exact location generated by GPS SIM28ML module to the predefined governing bodies who are responsible for maintenance of the roads.